Issues of Caribou Management in Northeastern British Columbia - Harrison, Scott; Surgenor, John (Rangifer, 1996)
Woodland caribou inhabit most of Northeastern British Columbia. They live across a variety of climatic and geographic gradients and in areas with as many as seven other ungulate species and seven predatory species. This apparent variability in habitat use may suggest that caribou in the Northeast are wide ranging and ecologically plastic. Conversely, caribou in Northeastern B.C. may live in discrete groups that have adapted to local conditions. There are few published data of woodland caribou in Northeastern B.C. Information is lacking on the number of caribou, their seasonal movements, their habitat requirements, and their interactions with other species. Logging, seismic activity, pipeline construction, oil and natural gas drilling, hydro-electric dams, and prescribed burning have all impacted habitat in previously undeveloped areas. The manner and rate at which these activities are changing habitats far exceeds our growth in knowledge of caribou ecology. Given this combination of few data and rapid habitat alteration, resource managers cannot know the impact of these habitat changes. We believe that this jeopardises the conservation of viable caribou populations.